1994
DOI: 10.1002/ajh.2830470112
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐annexin V antibody in systemic lupus erythematosus patients with lupus anticoagulant and/or anticardiolipin antibody

Abstract: We investigated anti-annexin V antibody (aANX) in patients with systemic lupus erythematosus (SLE), and correlated to positivity with lupus anticoagulant (LA)/anticardiolipin antibody (aCL). aANX was positive in 12/47 SLE patients (26%), including 7 with beta 2-glycoprotein 1 (GPI)-dependent aANX. The positivity of aANX was higher in patients with aCL (19%) and LA/aCL (50%) than in those without LA/aCL (10%). From these results, it is concluded that aANX is an autoantibody closely related to LA/aCL, and can be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
51
1
1

Year Published

1997
1997
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(53 citation statements)
references
References 7 publications
0
51
1
1
Order By: Relevance
“…These auto-antibodies are heterogeneous, and encompass a broad range of target specificities and affinities, all recognizing various combinations of phospholipids and/or phospholipid-binding proteins [2,3]. While aPL were initially believed to target anionic phospholipids directly, we now appreciate that aPL recognize primarily phospholipid-binding proteins that interact with anionic phospholipids, such as β2-glycoprotein I (β2GPI), prothrombin (PT), and annexin V [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…These auto-antibodies are heterogeneous, and encompass a broad range of target specificities and affinities, all recognizing various combinations of phospholipids and/or phospholipid-binding proteins [2,3]. While aPL were initially believed to target anionic phospholipids directly, we now appreciate that aPL recognize primarily phospholipid-binding proteins that interact with anionic phospholipids, such as β2-glycoprotein I (β2GPI), prothrombin (PT), and annexin V [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…They are associated with a clinical syndrome of thrombosis and/or recurrent fetal loss (1,2). Although aPL were initially believed to target anionic phospholipids (PL) directly, they are now thought to recognize primarily PL-binding proteins that interact with anionic PL, such as ␤ 2 -glycoprotein I (␤ 2 GPI), annexin V, and prothrombin (PT) (3)(4)(5)(6)(7). Recent work has shown that certain aPL recognize these PL-binding proteins alone, whereas other aPL require the presence of PL for this recognition (8 -10).…”
mentioning
confidence: 99%
“…In 1994, Matsuda et al [2] first described positive a-A5 in 26% of patients with systemic lupus erythematosus (SLE) and suggested that this antibody could be an independent risk factor in these patients. Three years later, Kaburaki et al [29] found positive a-A5 in 19% of SLE patients and emphasized that these antibodies are found more frequently in patients with arterial and/or venous thromboses, intrauterine fetal loss and prolonged APTT, as well as in SLE patients with negative APL.…”
Section: Significance Of the Determination Of A-a5 In Patients With Smentioning
confidence: 99%